2020
DOI: 10.1007/s10433-020-00566-7
|View full text |Cite
|
Sign up to set email alerts
|

Suffering in silence: a qualitative study of older adults’ experiences of living with long-term musculoskeletal pain at home

Abstract: Long-term musculoskeletal pain is a major, disabling, and often undertreated health problem among the increasing number of older adults worldwide. However, there is limited knowledge of community-dwelling older adults' experiences of living with this type of pain. The aim of the study was to deepen the understanding of the phenomenon: how older adults experience living with long-term musculoskeletal pain at home. The study design was an inductive qualitative Reflective Lifeworld Research approach grounded in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
0
12
0
2
Order By: Relevance
“…Likewise, Fowler et al [ 8 ] documented that “people who reported difficulty adjusting to a long-term IUC frequently described themselves as socially isolated and were more likely to have poor support systems and multiple conditions”. Catharina et al also documented, on loneliness and restrictions in daily living, that “restrictions in life influence the mood: “you become grumpy” and depressed and even irritated” which leads to the avoidance of social interaction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Fowler et al [ 8 ] documented that “people who reported difficulty adjusting to a long-term IUC frequently described themselves as socially isolated and were more likely to have poor support systems and multiple conditions”. Catharina et al also documented, on loneliness and restrictions in daily living, that “restrictions in life influence the mood: “you become grumpy” and depressed and even irritated” which leads to the avoidance of social interaction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experience of chronic pain as suffering predetermines significant changes in the perceptions of oneself and of the world [16]. A qualitative study identifies that the loneliness, the sense of not being taken seriously by health care providers and the fear of an uncertain future reinforced the suffering of chronic pain [17].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Previous studies of people’s experiences with chronic pain revealed feelings of restriction, loss and limitation of daily life, 12 13 loneliness and silent suffering. 14 These studies also showed that chronic pain had a pronounced effect on relationships, family life and work. 13 In addition, being on sick leave negatively affects a person’s life.…”
Section: Introductionmentioning
confidence: 95%
“…Qualitative pain research has been increasing in recent years, exposing aspects of pain experience that is not accessible through other approaches 11. Previous studies of people’s experiences with chronic pain revealed feelings of restriction, loss and limitation of daily life,12 13 loneliness and silent suffering 14. These studies also showed that chronic pain had a pronounced effect on relationships, family life and work 13.…”
Section: Introductionmentioning
confidence: 99%